The role of anxiety in shaping bystander behavior: A study of students in bullying situations in Indonesian high schools - Nengsih, Nengsih; Ilyas, Sabrida M.; Nasution, Silviarisa Br. (Program Studi Bimbingan dan Konseling Islam IAIN Langsa, 2024)
The bystander effect is a social phenomenon in which an individual's likelihood of helping others in an emergency decreases. Barriers preventing bystanders from intervening include anxiety about taking inappropriate actions and fear of becoming the next victim. This study aims to describe the level of anxiety among students in bullying situations and to examine the relationship between anxiety and the bystander effect in such contexts. A quantitative correlational research design was employed to explore the relationship between the independent and dependent variables. The study involved 154 high school students aged 16 to 18 years. Data were collected using researcher-developed anxiety and bystander effect scales, and analyzed using Pearson correlation. The findings indicate a significant positive relationship between anxiety and the bystander effect among students in bullying situations, meaning that higher anxiety levels are associated with a stronger bystander effect. These results suggest that school counseling services should prioritize interventions that address student anxiety and promote proactive bystander behaviors. Implementing programs focused on anxiety management and safe intervention strategies can play a vital role in reducing the incidence of passive bystander behavior in bullying cases.